2009
DOI: 10.4149/neo_2009_02_114
|View full text |Cite
|
Sign up to set email alerts
|

The p53 codon 72 polymorphism and susceptibility to colorectal cancer in Korean patients

Abstract: TP53 is a major gene involved in the determination of proliferation or growth arrest at the cellular level. The polymorphism of p53 at codon 72 has been widely studied; this variation has been associated with cancer susceptibility and disease outcome. The specific aim of this study was to investigate whether the p53 codon 72 polymorphism is associated with individual susceptibility to colorectal cancer in Korean patients. The frequency of the polymorphism was examined in 156 patients with colorectal cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Genotype p53 Arg72Pro as well as younger patients have decreased CRC risk in comparison to Pro72Pro and older age group of patients (0.14; 95% CI 0.02-0.99, p=0.049). Our results are consistent with the recent published studies [12,13,[42][43][44]. Few other studies have reported contradictory findings, e.g.…”
Section: Product Of Pcr-rflp Analysis Of Egf A61g (Left) and P53 Arg7supporting
confidence: 83%
“…Genotype p53 Arg72Pro as well as younger patients have decreased CRC risk in comparison to Pro72Pro and older age group of patients (0.14; 95% CI 0.02-0.99, p=0.049). Our results are consistent with the recent published studies [12,13,[42][43][44]. Few other studies have reported contradictory findings, e.g.…”
Section: Product Of Pcr-rflp Analysis Of Egf A61g (Left) and P53 Arg7supporting
confidence: 83%
“…From North India, association of Pro/Pro genotype with the increased risk of breast cancer (Sayeed et al, 2010), colorectal cancer and urinary bladder cancer (Pandith et al, 2010) has been previously reported in Kashmiri population inhabiting a mountainous region. Association of Pro allele with increased risk of colorectal cancer has been reported in Japanese population (Hamajima et al, 2002), Korean population (Cao et al, 2009), in Chinese (Zhu et al, 2007) and in Malaysian population (Aizat et al, 2011). But for breast cancer risk no association of p.R72P polymorphism have been reported in Tunisian (Mabrouk et al, 2003) and Russian subjects (Suspitsin et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…The change of amino acid from arginine to proline in a proline-rich region of the protein may affect the role of p53 in apoptosis (13). To date, a small number of case-control studies have been conducted to investigate the potential association of the CCND1 G870A and TP53 C215G polymorphisms with CRC susceptibility risk in various populations (14,15). However, no reports are available from Malaysian populations.…”
Section: Introductionmentioning
confidence: 99%